Circular economy proposal for the management of coffee waste in coffee shops in the city of lima in Peru - Díaz-Garay, Bertha (2024)
The processing of coffee for consumption in cafeterias generates significant amounts of waste, mainly coffee husks that, when roasted, ground and passed through coffee machines, generate spent coffee. The problem found is that there is no adequate management of this waste, nor are the waste generated quantified. This research seeks to identify alternatives to solve this problem. The research has an exploratory scope, using a survey with a convenience sample of 18 coffee shops, to obtain information about the interest in participating in a coffee waste collection model. Likewise, a cluster model was used to identify the best way to collect waste, for this the location of 72 cafeterias in the study area was determined. As a result, it is concluded that there is interest in the reuse of spent coffee by applying an appropriate waste collection model by conglomerates.